1996
DOI: 10.1016/0014-5793(96)00011-7
|View full text |Cite
|
Sign up to set email alerts
|

The 170 kDa glucose regulated stress protein is a large HSP70‐ HSP110‐like protein of the endoplasmic reticulum

Abstract: The existence of a family of unusually large and highly diverged hsp70-1ike proteins (the hspll0/SSE family) has recently been described. The 170 kDa glucose regulated stress protein (grpl70) is a retained endoplasmic reticulum glycoprotein that may be involved in immunoglobulin folding and/or assembly. We describe here the cloning of the cDNA for grpl70 and show that it, like hspll0, is a large and highly diverged hsp70-1ike polypeptide which shares specific features with hsp70 (the dnaK family) and the hspll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
75
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 20 publications
0
75
0
Order By: Relevance
“…Hsp110 and grp170 both appear to exhibit a peptide-binding cleft (11,18,44). However, hsp110 and grp170 differ dramatically from the hsc70s in their C-terminal domains, which, in the case of hsc70 proteins, appear to function as a "lid" for the peptide-binding cleft and may have an important influence on the properties of the bound peptide/protein and/or the affinity for the associated peptide/ protein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hsp110 and grp170 both appear to exhibit a peptide-binding cleft (11,18,44). However, hsp110 and grp170 differ dramatically from the hsc70s in their C-terminal domains, which, in the case of hsc70 proteins, appear to function as a "lid" for the peptide-binding cleft and may have an important influence on the properties of the bound peptide/protein and/or the affinity for the associated peptide/ protein.…”
Section: Discussionmentioning
confidence: 99%
“…Less is understood at the molecular level of grp170 structure and function; however, cellular studies have shown that it binds to Ig chain in the ER, may be the ATPase responsible for protein import into the ER, and actively binds peptides from TAP (i.e., the transporter associated with Ag processing; Refs. 11,19,20,23,24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Six of these up-regulated proteins were unequivocally identified on the basis of amino acid sequence data obtained from tryptic peptides eluted from the relevant gel spot ( Table 1). Five of these [170 kDa GRP, endoplasmin, BiP, calreticulin, endoplasmic reticulum protein 5 (ERP5)], correspond to proteins whose status as ERresident molecular chaperones has been described [8,[26][27][28]. A further protein (spot 7, Figure 2), induced in response to NSP4 * Numbers refer to protein spots identified in Figure 2.…”
Section: Expression Of Nsp4 Up-regulates the Synthesis Of Several Celmentioning
confidence: 99%